2011
DOI: 10.4021/cr18w
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bioimpedance to Assess Changes in Hemodynamics During Acute Administration of CPAP

Abstract: BackgroundAttempts to investigate the mechanisms by which continuous positive airway pressure (CPAP) therapy improves heart function in patients with obstructive sleep apnea (OSA) have been limited by the lack of non-invasive methods to assess cardiac performance. We used transthoracic electrical bioimpedance (TEB) to assess acute hemodynamic changes including heart rate (HR), stroke volume (SV), cardiac output (CO) and cardiac index (CI) during PAP titration in (1) post-operative cardiac surgery patients, (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Cardiac output was not measured during the experiment, but it is unlikely that there was a systematic difference between the two subject groups given their young age. Any change in cardiac output resulting from CPAP was likely to be comparable in both groups, considering that therapeutic CPAP was similar in both groups (see Table 1) (20,31). Pulmonary function tests revealed that there was no significant differ- ence in vital capacity (VC) or in functional residual capacity (FRC) between the groups (see Table 2), discarding the possibility that increased PG was associated with low lung volumes.…”
Section: Stability Markersmentioning
confidence: 98%
“…Cardiac output was not measured during the experiment, but it is unlikely that there was a systematic difference between the two subject groups given their young age. Any change in cardiac output resulting from CPAP was likely to be comparable in both groups, considering that therapeutic CPAP was similar in both groups (see Table 1) (20,31). Pulmonary function tests revealed that there was no significant differ- ence in vital capacity (VC) or in functional residual capacity (FRC) between the groups (see Table 2), discarding the possibility that increased PG was associated with low lung volumes.…”
Section: Stability Markersmentioning
confidence: 98%
“…Even the acute administration of CPAP may have profound cardiovascular effects. Several studies have reported that acute CPAP administration decreases stroke volume and cardiac output in patients with CHF and OSA [ 71 , 72 ], and one recent study found similar decreases in stroke volume and cardiac output in a range of patients including OSA patients without CHF, post-operative cardiac surgery patients, as well as healthy volunteers [ 73 ]. However, these findings have not been consistently reported [ 74 , 75 ] and the acute cardiovascular effects of CPAP are not fully understood.…”
Section: Effects Of Osa Therapy On Afmentioning
confidence: 99%